Research on health transition in Africa: time for action - Maher Dermot; Sekajugo James (BMC, 2011)
Abstract With rapidly increasing globalization, trends towards unhealthy diets, obesity, sedentary lifestyles and unhealthy habits are resulting in an increased worldwide burden of chronic non-communicable diseases (NCDs). In Africa this means that health systems face the challenge of an increasing burden of NCDs and of continuing high morbidity and mortality from communicable diseases. This health transition represents an enormous challenge to Africa as the region with the least resources for an effective response. Whereas previous epidemics, including HIV, have caught Africa unprepared, the opportunity now arises to take the advancing wave of health transition in Africa seriously. Health research has a key role to play in meeting health and development goals, and must be responsive to changing disease patterns, such as health transition. There is an urgent need for research on health transition in Africa to enable countries to respond effectively to rapidly changing health needs. Key areas of research include the following: epidemiological research so that a good understanding of the distribution in Africa of communicable and non-communicable diseases can inform health planning; research on the interactions between communicable and non-communicable diseases; health system research with a particular focus on new approaches to improve the primary care response to health transition; and policy research to evaluate the more upstream measures addressing the population-level determinants of NCDs. It is time to capitalise on the global policy environment, which is becoming more favourable to action on health transition in Africa, and implement a research agenda for health transition. Alliances have a key role to play in Africa as well as in other regions in implementing the research agenda on health transition by building research capacity and mobilizing the necessary investments.